An improved Equivalent Circuit Model for Nonlinearly Loaded Receiving Structures subject to High Power Electromagnetic Pulses - Michels, R.; Schaarschmidt, M.; Gronwald, F. (URSI General Assembly and Scientific Symposium (Online), 2020)
Equivalent circuit models of receiving structures are commonly used to include lumped elements with nonlinear current-voltage characteristics into an EMC analysis. In this contribution an efficient method will be introduced to derive an equivalent circuit model of a loop-antenna that includes a diode as a nonlinear load. The relevance of this circuit model will be illustrated by studying the response of this antenna to repetitive HPEM pulses.